Preparedness of Community Hospital Against COVID-19 - Prajapati, Ijendra; Kayastha, Gyan (Journal of Lumbini Medical College, 2020)
Government of Nepal (GoN) imposed a nationwide lockdown on 24th March, 2020 with an effort to limit the spread of novel corona virus which is responsible for corona virus disease (COVID-19). COVID-19 Nepal: Preparedness and Response Plan (NPRP) was implicated on April 2020 which stated Sukraraj Infectious and Tropical Disease Hospital (STIDH) in the capital, Kathmandu has been designated by the GoN as the primary hospital along with Patan Hospital and the Armed Police Forces Hospital in the Kathmandu Valley. The Ministry of Health and Population (MoHP) had requested the 25 hub and satellite hospital networks across the country; designated for managing mass casualty events; to be ready with infection prevention and control measures, and critical care beds where available.Hospitals with less than 50 beds viz community-based municipality hospitals were left feeble against the surge of the pandemic. Waiting for the aid and support from government was the only option for some hospitals that lacked resources to combat this invisible culprit of global pandemic. However, Nepal Korea Friendship Municipality Hospital (NKFMH) located in Thimi, Bhaktapur determined itself to fight against this pandemic withlimited resources. This hospital not only serves the local community but also patients coming from all over Province 3 due to government insurance facilities provided by this hospital. With interaction and support from the Hospital Director, Mayor of the municipality, Korea International Cooperation Agency (KOICA), Bhaktapur Red Cross, Hospital board, Hospital Staffs, Medical Team, Adminstration, Interpid and locals in the community prompt preparedness action plan was formulated through various meeting at different levels and acted upon.